Sickness and disability systems: comparing outcomes and policies in Norway with those in Sweden, the Netherlands and Switzerland - Hemmings, Philip (OECD Economics Department Working Papers, 2020)
In Norway, sick-leave compensation and disability benefit is comprehensive and an important component of employee rights and benefits. However, despite policy attention, use of these systems is excessive; sickness absence and disability benefit recipiency levels remain extraordinarily high compared with other countries. This paper compares Norway's reform experience and policy settings with those of three countries that also have comprehensive support and that have faced similar problems: Sweden, the Netherlands and Switzerland. All four countries have made a number of changes to sick leave and disability benefit systems. However, it appears that Norway's reforms have so far been rather less successful. A broad impression in comparing the reforms is that Norway has conducted fewer measures involving reductions to entitlements and improvements in work incentives compared with the other countries